2005
DOI: 10.1021/la0509347
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Probing Investigation of the Mechanism of Formation of MSU-type Mesoporous Silica Prepared in Fluoride Medium

Abstract: The mechanism of formation of a MSU-type siliceous material from tetraethyl orthosilicate (TEOS) in the presence of the nonionic surfactant tergitol T-15-S-12, sulfuric acid, and sodium fluoride has been investigated using mainly fluorescence probing techniques and, to a lesser extent, dynamic light scattering (DLS) and 29Si NMR spectroscopy. The tergitol micelles present in the systems obtained by progressively generating the reaction mixture giving rise to the mesostructured material by adding to an appropri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 46 publications
2
6
0
Order By: Relevance
“…These results are in good agreement with those recorded in the case of the hydrolysis of tetraethoxysilane, a precursor totally different from the perorganotins used in this study, in the presence of a nonionic surfactant. In that case, fluorescence probing investigations showed that the surfactant micelles do not interact with the inorganic precursor of the material, the siliceous species do not bind to the micelles, and the condensation of silica occurs in the aqueous phase.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…These results are in good agreement with those recorded in the case of the hydrolysis of tetraethoxysilane, a precursor totally different from the perorganotins used in this study, in the presence of a nonionic surfactant. In that case, fluorescence probing investigations showed that the surfactant micelles do not interact with the inorganic precursor of the material, the siliceous species do not bind to the micelles, and the condensation of silica occurs in the aqueous phase.…”
Section: Resultssupporting
confidence: 91%
“…The polar surface of hybrid particles should interact with the poly-(ethylene oxide) chains of the surfactant, as it was already reported for silica surfaces. 6,22 This complexation could hinder interparticular condensation and lead to a more divided hybrid, which would result in a higher specific surface.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A rapid but small increase in micellar size is observed within the first 3000 s and is consistent, considering the hydrocarbon chain length and amino acid headgroup, with the formation of spherical micelles. In the mechanistically very different fluoride-assisted formation of MSU-type mesoporous silica, a similar behavior was found …”
Section: Resultssupporting
confidence: 71%
“…They combined very nicely in situ EDXRD as well as multinuclear NMR ( 29 Si,17 O, 14 N) techniques; however, reactant molar ratios needed to be adapted to the employed techniques in order to optimize the experiments, and ended up to be quite far from the SBA-1 synthetic conditions. Lesaint et al 31 investigated the formation of the 2D-hexagonal SBA-We will show that it can be elegantly combined with SAXS experiments that will track the appearance and development of long-range order in various systems. A whole picture of the material synthesis can thus be obtained, starting from time t=0 when the inorganic precursor is added to the surfactant solution, until the recover from solution of the precipitated silica-surfactant mesophase powder (Figure 1).…”
Section: Ft-irmentioning
confidence: 99%